PEMANFAATAN LIMBAH IKAN TUNA MENJADI PRODUK OLAHAN MAKANAN DENGAN KONSEP ZERO WASTE UNTUK MENINGKATKAN EKONOMI MASYARAKAT KAWASAN TELUK TOMINI - Lantu, Iin Susilawati; Ahmad, Indra G; Fachrussyah, Zc; Arman, Veggy (Jurnal Abdi Insani, 2024)
Olimeyala Village is a village that has capture fisheries potential that has not been utilized optimally, especially in fishery product processing activities. So far, the use of fishery products is still limited to using meat, giving rise to quite high amounts of fishery waste. Therefore, the use of tuna fish by-products or waste (fish skin and fish bones) with a zero waste concept into processed fish cracker food is an effort to prevent environmental pollution due to the large amount of fishery waste. This service activity aims to educate and train the skills of the Olimeyala Village community and as an alternative business to improve the economy of the Olimeyala Village community. The method used in this activity is skills training in the form of a demonstration about the use of tuna waste into processed food products with a zero concept. The training provided is processing fish skin and tuna bone by-products into fish crackers. Training activity on making crackers from waste fish bones and fish skin into crackers. This activity of utilizing tuna fish waste into food products with the Zero Waste concept has a positive impact on the community in Olimeyala Village and will reduce environmental pollution caused by fishery waste